"Modernidades" moçambicanas, crise de referências e a ética no programa de filosofia para o ensino médio - Antonio Cipriano Parafino Goncalves (2009)
The work presents the resulties of studies that we have been conducting, regarding the proposal of our Doctoral Thesis in Education; it discusses the relation between Ethics and Education, focusing on Mozambique.Conceived as a philosophical reflection about Morals, Ethics was included in the Philosophy program to solve what the official documents name as a 'moral deficit', which would be ubiquitous in the country. This would be the result of the absence of Philosophy in the local High School, banned after the independence (1975). We allege that in Mozambique, more than in a moral deficit, one lives in a crisis of ethical-normative references, as a consequence of, beyond the influence of western modernity, the two modernities, through which the country has gone: the socialist revolutionary and the on going capitalist neoliberal. To support the thesis, we firstly did a documental research on the process of reintroduction the teaching of Philosophy , trying to examine the pedagogical place of Ethics. Then we proceeded to a bibliographical revision on modernity and its ethical consequences, so as to examine the Mozambican modernities and their ethical consequences. In the empirical domain, we interviewed in Maputo, from September to December 2007, the main intellectuals involved in the process of reintroduction of Philosophy in the country's High School. The results suggest that there is a contradiction in the Ethics conception wich is present in that Philosophy programm: from philosophical reflection about moral, the Ethics ends in moral education, a way refused by the main intellectuals involved in the process of reintroduction of Philosophy in the country's High School.